The Effect Of The Cooperative Integrated Reading and Composition (CIRC) Learning Model on Summary Writing Skills In Grade V - Sianipar, Jonatan Juliater; Siagian, Asister Fernando; Purba, Nancy Angelia (Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to determine the impact of the Cooperative Integrated Reading and Composition (CIRC) learning model on summary writing skills among fifth grade students at UPTD SDN124405 Pematangsiantar. The population in this study includes all fifth-grade students, while the sample consisted of 23 students selected using proportional random sampling. This research employs a quantitative approach and falls under the category of pre-experimental research, using a One-Group Pretest-Posttest Design. The researcher used an instrument consisting of 6 essay questions. This instrument was used to assess the influence of the problem-based learning model on students’ summary writing skills in Indonesian language learning. Data were collected through observation, tests, and documentation. After data collection, the analysis was conducted using Aiken's V Index and the N-Gain Test. The results of the N-Gain test showed that the average pretest score in the experimental class was 37.67, and the average posttest score was 85.53, resulting in a gain of 0.78. This indicates that the experimental class experienced a significant improvement in creative thinking skills, falling into the “very high” category (g ≥ 0.7). Based on these results, it can be concluded that the Cooperative Integrated Reading and Composition (CIRC) learning model has a positive effect on the summary writing skills of fifth-grade students at UPTD SDN 124405 Pematangsiantar in the 2023/2024 academic year